2021
DOI: 10.3390/ani11102885
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Evaluation of Derived Reactive Oxygen Metabolites and Biological Antioxidant Potential in Donkey Mares and Foals

Abstract: Our aim was to measure the concentrations of derived reactive oxygen metabolite (d-ROMs) and biological antioxidant potential (BAP) of donkey mares and foals at delivery and to verify the protective role of the placenta against fetal oxidative stress. A total of 15 Amiata jennies with a physiological gestation length and delivery were included together with 17 foals (two twin foalings). After delivery, maternal and foal venous blood samples were collected along with blood from the artery. Circulating lactate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Vakilian et al [65], comparing both modes of delivery using thiobarbituric reactive substances (TBARS) as markers of lipid peroxidation, total antioxidant power (TAP), and total thiol molecules (TTM) in the blood of mothers and their newborns, showed that natural childbirth causes an increase in OS compared to cesarean section. Sgorbini et al [66] showed the same relationship when studying reactive oxygen metabolites (d-ROMs) and biological antioxidant potential (BAP), noting the effective antioxidant defense of newborns, who often coped with ROS better than their mothers.…”
Section: Oxidative Stressmentioning
confidence: 83%

Oxidative Stress in Pregnancy

Grzeszczak,
Łanocha-Arendarczyk,
Malinowski
et al. 2023
Preprint
“…Vakilian et al [65], comparing both modes of delivery using thiobarbituric reactive substances (TBARS) as markers of lipid peroxidation, total antioxidant power (TAP), and total thiol molecules (TTM) in the blood of mothers and their newborns, showed that natural childbirth causes an increase in OS compared to cesarean section. Sgorbini et al [66] showed the same relationship when studying reactive oxygen metabolites (d-ROMs) and biological antioxidant potential (BAP), noting the effective antioxidant defense of newborns, who often coped with ROS better than their mothers.…”
Section: Oxidative Stressmentioning
confidence: 83%

Oxidative Stress in Pregnancy

Grzeszczak,
Łanocha-Arendarczyk,
Malinowski
et al. 2023
Preprint
“…In fact, the tissue damage during the peripartum period may lead to an inflammatory response. Furthermore, the progressive increment of metabolic activity during pregnancy may induce an oxidative stress status in animals, linked to inflammation [51]. The ADA is a ω-6 that can further predispose animals to oxidative stress though an influence on antioxidant system expression, such as superoxide dismutase (SOD) and glutathione peroxidase (Gpx) [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, donkey farming is becoming more popular due to donkey milk being used as an alternative to cow’s milk for children’s intolerances and in the cosmetic industry due to its organoleptic properties [ 2 , 3 ]. With the increasing interest in donkeys as dairy animals, studies concerning their health and welfare have been raised [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%